Acoustic signature of plastic marine debris mimics the prey items of deep-diving cetaceans - Greg B. Merrill; Z.T. Swaim; I.G. Benaka; A.L. Bishop; N.A. Kaney; S. Kuhlman; J.C. Matheson; E. Menini; S. Goh; S. Lei; D.P. Nowacek (Marine Pollution Bulletin, 2024)

Ex vivo and in vitro methods as a platform for studying anthropogenic effects on marine mammals: four challenges and how to meet them - Juan Manuel Vazquez; Jane I. Khudyakov; Carla B. Madelaire; Céline A. Godard-Codding; Heli Routti; Emily K. Lam; Elizabeth R. Piotrowski; Greg B. Merrill; Jillian H. Wisse; Kaitlin N. Allen; Justin Conner; Pierre Blévin; et al. (Frontiers in Marine Science, 2024)
Marine mammals are integral to global biodiversity and marine health through their roles in coastal, benthic, and pelagic ecosystems. Marine mammals face escalating threats from climate change, pollution, and human activities, which perturb their oceanic environment. The diverse biology and extreme adaptations evolved by marine mammals make them important study subjects for understanding anthropogenic pressures on marine ecosystems. However, ethical and logistical constraints restrict the tractability of experimental research with live marine mammals. Additionally, studies on the effects of changing ocean environments are further complicated by intricate gene-environment interactions across populations and species. These obstacles can be overcome with a comprehensive strategy that involves a systems-level approach integrating genotype to phenotype using rigorously defined experimental conditions in vitro and ex vivo . A thorough analysis of the interactions between the genetics of marine mammals and their exposure to anthropogenic pressures will enable robust predictions about how global environmental changes will affect their health and populations. In this perspective, we discuss four challenges of implementing such non-invasive approaches across scientific fields and international borders: 1) practical and ethical limitations of in vivo experimentation with marine mammals, 2) accessibility to relevant tissue samples and cell cultures; 3) open access to harmonized methods and datasets and 4) ethical and equitable research practices. Successful implementation of the proposed approach has the potential impact to inspire new solutions and strategies for marine conservation.

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Microplastics in marine mammal blubber, melon, & other tissues: Evidence of translocation - Greg B. Merrill; Ludovic Hermabessiere; Chelsea M. Rochman; Douglas P. Nowacek (Environmental Pollution, 2023)

A growing crisis for One Health: Impacts of plastic pollution across layers of biological function - Margaret Morrison; Rafael Trevisan; Prabha Ranasinghe; Greg B. Merrill; Jasmine Santos; Alexander Hong; William C. Edward; Nishad Jayasundara; Jason A. Somarelli (Frontiers in Marine Science, 2022)
The global accumulation of plastic waste has reached crisis levels. The diverse and multilayered impacts of plastic on biological health prompts an evaluation of these effects from a One Health perspective, through which the complexity of these processes can be integrated and more clearly understood. Plastic particles ranging from nanometers to meters in size are found throughout every ecosystem on Earth, from the deepest marine trenches to the highest mountains. Plastic waste affects all layers of biological organization, from the molecular and cellular to the organismal, community, and ecosystem-levels. These effects are not only mediated by the physical properties of plastics, but also by the chemical properties of the plastic polymers, the thousands of additives combined with plastics during manufacturing, and the sorbed chemicals and microbes that are transported by the plastic waste. Using a One Health framework we provide an overview of the following themes: 1) ways in which plastic impacts global health across levels of biological organization, 2) how the effects of plastic interact between layers of biology, and 3) what knowledge gaps exist in understanding the effects of plastic within and between biological scales. We also propose potential solutions to address this growing crisis, with an emphasis on One Health perspectives that consider the oneness of animals, humans, and the environment.

A transdisciplinary approach to reducing global plastic pollution - Zoie Diana; Rachel Karasik; Greg B. Merrill; Margaret Morrison; Kimberly A. Corcoran; Daniel Vermeer; Evan Hepler-Smith; Nishad Jayasundara; Jeremy Pare; John Virdin; William C. Eward; Jason A. Somarelli; et al. (Frontiers in Marine Science, 2022)